How Frequently Does out-of Hospital Sudden Unexpected Infants Death Represent the Sudden Infant Death Syndrome? - Lika L. Nisevich; Oleg V. Krieger; Natalia S. Selyutina; Stanislav Y. Bernikov; Tatyana N. Konopleva; Igor N. Nikishtsev; Marina S. Pavlova (Педиатрическая фармакология)
Background. 19.6 % of all fatal cases among Russian children who died in the first year of life are registered out-of hospital, and they are usually sudden. Out-of-hospital sudden unexpected infant death (OSUID) could be confused with sudden infant death syndrome (SIDS) followed by the wide variation in the diagnostic indicators of the syndrome.The aim of the study is to reveal the pathological changes in the tissues and organs of 420 cases of OSUID (group 1) compared with 350 cases of death in the hospital (group 2), to estimate the conformity of the final diagnoses and to identify cases of OSUID, which were SIDS.Methods. From 2009 to 2016 pathoanatomical and virological study of the organs of 420 cases of OSUID (group 1) and 350 babies who died in a hospital were carried out.Results. It was established that the age of infants of the 1st group at the time of death in 71 % of cases corresponded to the age of SIDS. In terms of gestational age and body weight at birth babies of the 1st group turned out to be much more prosperous. Signs of rapid onset of death in this group: plethora of internal organs (83.3 %) and petechial hemorrhages (75.5 %) were present significantly more often than in the 2nd. In the 1st group, predominantly light acute respiratory viral infections (ARVI) with minimal pathologic signs and pneumonia were diagnosed, but pneumonia in 33.3 % not detected at autopsy. Purulent tracheobronchitis (0 and 21.4 %), bacterial pneumonia (6.3 and 26.3 %), a large area of lung damage (3.8 and 56.1 %) were detected much less frequently in the 1st group. In 38 % of the 1st group, pneumonia was the only cause of death, and in no case in the 2nd. Pathology of the cardiovascular system (55.2 and 87.7 %), central nervous system (58.6 and 90.9 %);urogenital system (34.8 and 62.9), inflammation of the membranes and brain tissue (21.9 and 70.0 %), signs of past or current intrauterine viral infection (29.5 and 64.0 %) in the 1st group was diagnosed much less frequently than in the 2nd, but congenital syphilis, HIV infection and hepatitis C — 3 times more often (12.9 and 3.7 %). The more frequent pathology of the adrenal glands in the 1st group (66.7 and 34 %) could cause inadequate responses to minimal exposure to external factors, including mild acute respiratory viral infections. The diagnosis of SIDS was made in 3 cases and in 3 more it was questionable. However, the presence of multisystemic pathology excludes the diagnosis of SIDS. The diagnosis of SIDS could be established in 30 cases in cases of slight ARVI without intoxication, shock liver or disseminated intravascular coagulation syndrome.Conclusion. The most cases of sudden death occurred in not obvious life-threatening conditions in socially disadvantaged families in the absence of adequate observation, diagnosis and treatment.